Needs Analysis for Oral Communication at the Workplace: A Case Study of English Language Requirements for Engineers in an Automotive Company - Abdullah Adnan, Mohamed; Noor Raha, Mohd Radzuan; Hafizoah, Kassim (Penerbit Universiti Malaysia Pahang, 2009)
In recent years, calls have been made for graduates to be proficient in oral, written and communication skills so that they can function effectively at the workplace (Crosling & Ward, 2002). In Malaysia, all sectors of industries including private and civil services demand that graduates should equip themselves with language and communication skills in order to play their role effectively at the workplace (Chang, 2004; Ungku Harun, 2004). Most importantly, employers expect the young graduates who enter the job market to possess adequate proficiency and skills of the English language (Chang, 2004; Phang, 2006). Lagging in these skills is one of the factors to local graduates' unemployment. To understand the employers' demand and fuljill this need, it is essential to carry out a need analysis on the requirements for language proficiency and communication skills as necessitated especially by the engineering employers. This paper therefore reports on a case study which aimed to explore the requirements for language skills among engineers and the communicative events where English is to be utilized. A former automotive engineer now an academician was interviewed using a semi structured interview for data collection. Results indicate that the dominance of the English language as an international language for all engineers in most of the communicative events is beyond dispute.